Family-Owned Firms between Agency Conflicts and Stewardship: Corporate Governance Factors Driving Firm Performance (Journal of Business and Management Research, 2016)
The performance of family-owned firms has been driven by factors relating to family ownership, family leadership, and external supervision. In this paper, we offer an empirical study investigating the effects of those corporate governance concerns. To serve the purpose, we conducted a survey on 121 Chinese family-owned firms over the period of 2012-2014. Using pooled ordinary least square technique we find that family leadership and external supervision significantly influence the firms' Return on Assets (ROA) and Return on Equity (ROE) whereas family ownership significantly influences ROA, but not ROE. Empirical findings also indicate that firm size, total assets and solidity have significant impact on ROA and ROE. Discussing our empirical findings in light of stewardship and agency theories, we especially supplement stewardship theory due to the close alignment between owners and managers in family-owned firms.Journal of Business and Management Research, vol.1 (2), 2016, pp. 33-47